Psychology of Hair Loss Patients and Importance of Counseling - Dhami, Lakshyajit (Indian Journal of Plastic Surgery, 2021)
Androgenetic alopecia (AGA) is highly prevalent in society, affecting both men and women. More than the sociological meaning of hair loss, it has become a very important part of self-identity or “body image.” A psychological concept of body image refers to one's thoughts, feelings, perceptions, and behavioral changes related to one's physical looks. In spite of alopecia's common occurrence, it often leads to psychological disturbance and distress. Hair thinning and perceived hair loss also has a very important negative impact on the psyche of the individual. The common emotional aspects associated are self-consciousness, embarrassment, frustration, and jealousy. Knowledge of these effects among the clinicians managing hair loss patients is beneficial. The clinician must make an active effort to identify the borderline group of patients with body dysmorphic syndrome so as to manage them with psychotherapeutic medication for their hair loss prior to hair transplantation. This article aims to provide important information and an understanding of how the psychology gets affected due to hair loss, particularly AGA and its management to the practicing hair transplant surgeons.
Keywords: hair loss; hair transplant; counseling; psychology; body dysmorphic disorder